The Relevance of Fiqh al-Hadis Methodology and the Sharh Method with the Application Approach - Sabir, Muhammad; Fathurrahman, Rezki Amalia; Ruhilawati, Ruhilawati (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2023)
The aim of the study was to explore the correlation between the methodologies of fiqh al-Hadith and Sharh with the practical application of Hadith. The research utilized qualitative literature review methods to investigate how the methodologies of fiqh al-Hadith and Sharh relate to the application of Hadith. The findings revealed that the methodology of fiqh al-Hadith involves four key steps: linguistic analysis, critical evaluation, Hadith analysis, and selection of authentic or weak Hadiths. For instance, the Hadith about buying and selling narrated by Muslim no. 2786 and Bukhari no. 2020 is considered authentic due to the consistency in its chain of narrators and its relevance to the topic. The benefits of fiqh al-Hadith and Sharh methodologies include their ability to apply Hadiths such as those related to buying and selling as outlined in Muslim no. 2786 and Bukhari no. 2020.